Pemberdayaan Santri Melalui Penerapan Akuaponik: (Studi Di Ponpes Anwarul Huda Malang) - Abadi, M Tommy Hasan; Saparullah; Dewi, Atika Puspita Sari; Mufti, Nandang (Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
The empowerement of santri is an important aspect in the improvement of the quality of santri resources. Pondok Pesantren Anwarul Huda Kota Malang committed to improve the quality of santri resources through entrepreneurship programm to all santris in addition learn about Islam. Considering geographical location of the Pesantren, which in the downtown with high population and buildings. Application of the aquaponics system in Pesantren can be an option to increase the empowerement of santri. The aquaponics system is an agricultural innovation that integrate two products, hydrophonics and fish tank. This programs aim is to optimize the distribute interest of santri and become an option to increase entrepreneurship programm in line with Pesantren. Furthemore, santri become more empowered, and have a bigger role so it could improve the quality of santri resources.